Acceptance of climate adaptation measures for transport operations: Conceptual and empirical overview. (December 2021) - Griese, Kai-Michael; Franz, Martin; Busch, Jan Niklas; Isensee, Carmen
Highlights: Development of a thereotic acceptance model for climate adaptation measures. Study empirically analyzes the acceptance phases for climate adaptation measures. Different acceptance phases require different support measures. Practical starting points for establishing climate adaptation measures. Abstract: Transport operations are climate sensitive. Despite this, scientific literature and corporate practice present little evidence on how corporate actors use climate adaptation measures to prepare their transport operations for climate change. This paper explores two research questions: How can the acceptance among corporate decision-makers towards climate adaptation measures for their transport operations be explained? Based on the Theory of Planned Behavior and the Diffusion of Innovations we develop a theoretical framework for dealing with climate adaptation measures for transport operations (step 1). We support the use of this framework through a literature review (1989–2020) (step 2) and semi-structured interviews with German companies that have implemented best practice measures (step 3). The results show that the handling of climate adaptation measures for transport operations can be described in three acceptance phases: acceptance of attitude, action, and use. We conclude that these phases determine the approaches required for promoting climate change adaptation.